Pengaruh Kecepatan Aliran Terhadap Kandungan COD Pada Pengolahan Air Limbah Kecap Secara Aerobic/Aaerobic - Endang Suryadi (Jurnal Kimia dan Kemasan, 1996)
Removal rate of COD varies with COD volume loading, aeration time and or flow rate of incoming waste water. Anaerobic process showed that the higher flow rate was continued the lower COD removal was yielded, whereas the aerobic pointed out that COD removal was obtained higher and higher as the flow rate was increased. Although coagulant was not used for this treatment, the experiment appeared to indicate a good result where average COD removal rate for Q1• Qz. Qjand Q4 are 93.8, 93.2, 91.0, and 92.4 % respectively.